2015
DOI: 10.1186/s40317-015-0082-3
|View full text |Cite
|
Sign up to set email alerts
|

Two methods of radio transmitter attachment and their effects on the behavior and energetics of captive long-tailed ducks (Clangula hyemalis) during winter

Abstract: Background: Attachment of external devices can have negative consequences for the health and fitness of subjects, but these effects are often overlooked. In preparation for a field study with small sea ducks, we investigated the effects of two types of external radio transmitter attachments on activity budgets and energetics of captive longtailed ducks (Clangula hyemalis) during winter. Methods:We conducted behavioral observations on 15 ducks over 3 months and measured oxygen consumption rates while resting on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Enstipp et al [24] compared tesasutured devices with subcutaneously anchored devices in Long-tailed Ducks and found that while birds with tesasutured devices recovered more rapidly from alterations of behaviour, tracking devices were lost after 26 days on average. Effects of other attachment methods were reported in original tracking studies.…”
Section: Other Attachment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enstipp et al [24] compared tesasutured devices with subcutaneously anchored devices in Long-tailed Ducks and found that while birds with tesasutured devices recovered more rapidly from alterations of behaviour, tracking devices were lost after 26 days on average. Effects of other attachment methods were reported in original tracking studies.…”
Section: Other Attachment Methodsmentioning
confidence: 99%
“…Paquette et al [60] found female Mallards with subcutaneously anchored backpacks to spend less time on egg laying and incubation and to initiate fewer nests. Enstipp et al [24] found strongly altered behaviour in Long-tailed Ducks Clangula hyemalis with subcutaneous attachments, with increased preening behaviour and less time spent on the water, and two out of five individuals developed a bacterial infection at the site of attachment. Radio transmitters attached with prong and suture had no effect on reproduction in Wood Ducks [36].…”
Section: Subcutaneous Attachmentsmentioning
confidence: 99%
“…Attachment of tracking devices may increase the susceptibility of birds to being predated or shot, as shown by causes of death from tagged greater white-fronted geese in this study, of which out of 35 birds, 14 had been retrieved as shot, and 7 as predated by large birds of prey or fox during the spring migration following tag deployment. This may be caused by a change in behavior (e.g., increased time spent preening, [13]) or reduced flight maneuverability by the cross-sectional profile of the backpack tag causing additional drag [4], and perhaps not so much hunters targeting for marked geese [6]. Although our study found negative effects on return rates, our survival rates of tagged individuals were definitively higher than in some other studies [39], Harness attachments may have negative effects on survival, but are also likely to have non-lethal effects on migratory birds [26].…”
Section: Discussionmentioning
confidence: 99%
“…External tags have been reported to have no significant long-term effect on animals [59,71,78], but there have also been cases showing various negative effects on animal behaviour and survival [22,43,63,65,79,80]. Such effects can be intensified if the animal is flying or moving through water, depending on tag placement [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…increased preening or biting the tag/harness [54,[58][59][60][61]. To decrease negative effects of tag aversion [62], it is necessary to shorten handling time and evaluate different types of tag placement and attachment methods for this species group [58,[63][64][65][66]. Welfare assessments should be made alongside considerations of data quality in order to balance animal discomfort against the amount and quality of scientific knowledge gained from the respective study [67].…”
mentioning
confidence: 99%